Perception of Stakeholders on the Maintenance Management Strategies for Sports Facilities in Selected Universities in Southwestern, Nigeria - E. Oseghale, Godwin; J. Ikpo, Ime; O. Oseghale, Bridget; D. Adetooto, Johnson (British Journal of Marketing Studies, 2019)
The paper identified and examined facilities maintenance strategies adopted in selected universities in south-western Nigeria, examined maintenance planning and factors influencing the choice of maintenance strategies adopted in the study area. Data were sourced using a structured questionnaire administered on sportsmen and women and the maintenance staff of the maintenance department in the universities sampled. The sample size captured all the fifteen games, featured in Nigeria university games association (NUGA) in the three federal universities that had such facilities for the fifteen games and have hosted the national and international sporting event were purposively selected. Data were analyzed using frequency distribution, percentages and mean response analysis. The findings revealed that the most influencing factors for the choice of maintenance strategies were maintenance policy with a mean score of (3.90), technological factors (3.85), maintenance standard (3.76), maintenance tactics (3.74), economic factors (3.74), and environmental factors (3.73). The study concluded that the most widely used maintenance strategy was reactive maintenance strategy and identified its problem to be the adoption of a piecemeal approach to the maintenance of facilities thereby resulting in under-maintenance of sports facilities.